Fun Learning Strategy in Learning Maharah Kalam at Markaz Arabiyah - Saleh, Ummu Sulaimah; Daroini, Slamet; Solihah, Mamluatu; el-Warfali, Sulaiman Hassan Sulaiman (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2025)
The dominance of conventional instructional methods in language education often results in rigid, less engaging learning environments. As a response, fun learning strategies have emerged as innovative approaches to enhance student enthusiasm and active participation. This study explores the implementation of fun learning strategies in teaching Maharah Kalam (speaking skills) at Markaz Arabiyah Pare. Employing a descriptive qualitative method within a case study framework, the research was conducted using the researcher as the primary instrument, supported by an interview guide. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model involving data reduction, data display, and conclusion drawing. Findings reveal that the fun learning strategy in Maharah Kalam instruction is implemented through four core activity types involving nine specific methods: (1) Daily activities, incorporating sualan (questioning) and games; (2) Thematic speaking practice, including drama, demonstration, promotion, and debate; (3) Daily evaluations such as Ashfudzihni; and (4) Monthly events like MC practice and taqdimul qishshoh (storytelling presentations). These strategies significantly contribute to Arabic language acquisition by increasing learner motivation, building self-confidence in speaking, and promoting active classroom participation. The study underscores the value of integrating creative, interactive methods into language instruction to support learner-centered education and communicative competence in Arabic.